Efficacy of fluoride varnishes with different compositions on white spot lesions remineralization - Torres, Carlos Rocha Gomes [UNESP]; Spinola, Manuela da Silva [UNESP]; Prado, Renata Falchete do [UNESP]; Rodrigues, Vinicius Anéas; Gutierrez, Natália Cortez [UNESP]; Borges, Alessandra Buhler [UNESP] (Editora Cubo, 2021)
Objective: To evaluate the efficacy of different fluoride varnishes on white spot lesions (WSL) remineralization. Material and Methods: Polished bovine enamel specimens were obtained (n = 60) and had their initial surface Knoop microhardness (SMH) determined. WSL were created and the SMH was measured again. Then, specimens were allocated into six groups: C – Control (without varnish); BF – Bifluorid 12 (6% NaF + 6% CaF2); DP – Duraphat (5% NaF); PF – Profluorid (5% NaF); FP - Fluor Protector (0.2% NaF + 0.9% difluorsilane); CW - Clinpro White Varnish (5% NaF + 5% TCP). After varnishes application, specimens were immersed in artificial saliva for 24 h. Then, pH-cycling was performed for 8 days and SMH was measured. Data were analyzed by one-way ANOVA and Tukey’s test. Results: Non-significant differences were observed among the groups at baseline (p = 0.187) and after WSL formation (p = 0.999). After treatments, significant differences were observed among the groups (p = 0.001). Mean % of alteration (SD) and results of Tukey test were: C- 92.40 (12.10)a; PF- 88.66 (10.66)a; FP- 85.90 (14.49)ab; BF- 67.85 (17.86)bc; CW- 66.60 (18.48)c; DP- 58.62 (8.69) c. Conclusion: Bifluorid 12, Clinpro White Varnish, and Duraphat showed higher efficacy than artificial saliva in promoting the remineralization of WSL, nevertheless, none of the treatments were able to recover sound enamel baseline microhardness.
Eficácia de vernizes fluoretados com diferentes composições na remineralização de manchas brancas
Keywords: Dental caries; Fluoride; Fluoride varnishes